Nonsurgical molding of congenital auricular deformities and analysis of the correction outcomes: A single-center, retrospective study in east China - Liu, Chuanbo; Wo, Peibin; Zhang, Jufang; Li, Jinsheng (Frontiers in Pediatrics, 2022)
Objective: Our research was carried out to provide clinical reference for the application of nonsurgical therapy in newborns with congenital auricular deformities in east China. Methods: A retrospective study of consecutive newborns using noninvasive ear molding was conducted in Hangzhou of east China’s Zhejiang Province. The demographic and clinical information, and photographs of ear before and after treatment were taken. The diagnosis of each auricular deformity was identified, and the treatment outcome was evaluated. Results: 224 patients including 356 congenital ear anomalies received noninvasive ear molding. The median age of infants to initiate treatment was 39.5 days. The median treatment duration was 42.5 days. The median follow-up time was 137.0 days. The overall treatment effective rate of all infants with nonoperative ear molding was 92.1 percent, and mild skin irritation and ulceration were occurred in 34 ear deformities (9.6 percent). It confirmed that the treatment efficiency was satisfactory and the complication rate was still acceptable despite late initiation treatment of neonates in east China. In further analysis of treatment outcomes among three subgroups of infants (the ages to initiate the ear molding were respectively less than or equal to 28 days, 29-56 days, and more than 57 days), it revealed initiation treatment was significantly related to the treatment results and the earlier the initiation treatment, the higher the effective rate and the lower the complication incidence. Conclusion: Our study hint that newborns in east China may have a longer time window period for correction. What’s more, although our study affirmed a longer time window period for noninvasive molding, early diagnosis and treatment is still recommended to improve therapy efficiency and reduce treatment duration and complication.